First report of the flea beetle genus Tegyrius Jacoby in Malaysia and Indonesia with descriptions of two new species (Coleoptera, Chrysomelidae, Galerucinae, Alticini) - Prathapan, K. D. (Zootaxa, 2026)
The flea beetle genus Tegyrius Jacoby (Coleoptera, Chrysomelidae, Galerucinae, Alticini) is newly reported from Malaysia and Indonesia. Tegyrius clarki sp. nov. from Malaysia and T. indonesiana sp. nov. from Indonesia are described and illustrated.